Clinical and economic impact of drug eluting beads in transarterial chemoembolization for hepatocellular carcinoma. (21st November 2014) - Vadot, L.; Boulin, M.; Guiu, B.; Aho, L. S.; Vourc'h, M.; Musat, A.; Hillon, P.; Lepage, C.; Guignard, M.‐H.; Fagnoni, P.
Summary What is known and objective Drug eluting beads (DEBs) theoretically improve the efficacy and safety of transarterial chemoembolization (TACE) in hepatocellular carcinoma (HCC). Nonetheless, their economic profile has not been assessed. Our retrospective before/after study aimed to compare efficacy, safety and economic profile of two strategies of TACE without (Period 1) or with the possibility of using DEBs (Period 2). Methods All HCC patients treated by TACE in our hospital between March 2006 and May 2013 were included. Economic analyses were performed from the French Public Health Insurance point of view according to the French Diagnosis‐Related Group prospective payment system and from the analytic accountability. Results and discussion One hundred and sixty‐one patients were included. Median time to treatment failure and overall survival were 13·1 and 23·8 months in Period 1 vs. 14·1 and 30·2 months in Period 2 (P = 0·45 and P = 0·40). Mean hospital durations and tariffs were 14·9 ± 7·7 days and € 11 472 ± 5901 in Period 1 vs. 12·4 ± 8·4 days and € 7654 ± 4625 in Period 2 (P = 0·03 and P < 10−4). What is new and conclusion The possibility of using DEBs did not improve the prognosis in HCC patients treated by TACE. Nonetheless, it had a better medico‐economic profile.